9514 1404 393
Answer:
a) -4
b) 11
c) a(1) = -4; a(n) = a(n-1) +11 (Maybe you want an = -4+11(n-1).)
d) 95
Step-by-step explanation:
See the attached.
a) The value of a1 is given in the problem statement. It is -4.
__
b) If we take "d" to mean the common difference between terms, it is the value added to one term to get the next term. The recursive formula shows that value is 11.
__
c) The iterative rule for the sequence is given in the problem statement.
We suspect the intention is to ask for the explicit rule. That rule has the form ...
an = a1 +d(n -1)
Using the values of a1 and d, we get the explicit rule ...
an = -4 +11(n -1)
__
d) The recursive/iterative rule requires you find all previous terms in the sequence before you can learn the 10th term. The explicit rule allows you to substitute n=10 and compute the 10th term directly:
a10 = -4 +11(10 -1) = -4 +99 = 95
The tenth term is 95.
_____
Additional comment
We'd rather not have to try to guess the intended question. Perhaps you should discuss this question with your teacher. (recursive vs. iterative vs. explicit)